Synthesis of Dihydropyridine, Alkylthiopyridine, Thienopyridine and Pyridothienopyrimidine Derivatives - K.K. EL-LOUH, ALI; M. ABUNADA, NADA; M. EL-ABBADY, SAMIA; EL-SHOUBAKI, M.J. (Asian Journal of Chemistry, 2010)
The reaction of arylidene cyanothioacetamide (1a,b) with acetylacetone (2) gave dihydropyridine derivatives (3a,b). Compounds (3a,b) on reaction with some halogenated derivatives (5A-C) to afford 2-alkylthiopyridine derivatives (6-8). The compounds (3a,b) reacted with (5A-G) to give thieno[2,3-b]pyridine derivatives (9-13). The compounds (9, 10) reacted with formic acid, (9) with formamide, and (10) with acetic anhydride to give (14-16), respectively.